Correlation of open cell structure with properties of green rubber foam from epoxidised natural rubber/reclaimed rubber glove / M.A. Mahamood...[et al.] - M.A., Mahamood; N., Mohamad; A.R., Jeeffeerie; A.H., Mohd Zain (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
A promising impact absorber foam material was produced from epoxidised natural rubber (ENR) and reclaimed rubber (RR) with the addition of sodium bicarbonate (SBC) as a blowing agent. This study is part of our effort to develop green rubber foam from reclaimed rubber from glove. It focuses on the effect of different ENR/RR ratio of 100/0, 90/10, 70/30, 50/50, 30/70 and 0/100. The samples were prepared by melt compounding using a Haake internal mixer and expanded via two step heat transfer foaming process. The physical characteristics (expansion ratio, density and water absorption) and impact absorption by drop ball testing of ENR/RR foams were studied. The results showed significant correlation between the rubber blend ratios with generated pore structures towards the properties of the foams. From the experimental values, ENR/RR with the ratio of 90/10 yielded the rubber foam with the highest relative density of 0.85 as well as the lowest water absorption rate of 0.1 g/hrs. This foam cell characteristics resulted in improved energy absorption behaviour. Sample with optimum pore size of ~0.36 mm shows the highest energy absorption of up to 0.65 joules compared to others.